KEMAMPUAN MAHASISWA DALAM MENYELESAIKAN SOAL-SOAL HOTS PADA MATERI PAI SEKOLAH/MADRASAH - Awal Fikri Baharsyah; Muhammad Fauzi; Sabarudin; Yayan Suprapni (Jurnal Tawadhu, 2023)
The rapid development of science and technology requires humans to have higher order thinking skills. Education in general places more emphasis on the cognitive domain, HOTS is a thinking ability that not only remembers but is also expected to be able to develop ideas. The purpose of this descriptive study was to find out about the ability of PAI students to complete and compose HOTS questions, as well as the factors that influence students' ability to solve HOTS questions on PAI material. Qualitative research methods are strengthened by simple quantitative data. The descriptive form in this study is a case study. The population in this study were 34 students of Islamic Religious Education semester IV class B FTIK UIN Raden Fatah Palembang. The data collection method uses questionnaires, HOTS questions, draft questions and interviews. While the analysis technique uses inductive techniques. The results of this study indicate that students' ability to solve HOTS questions tends to have sufficient ability and is still low in solving questions in the cognitive domains C5 and C6. Then the factors that affect students' ability to work on HOTS questions include, students are not used to working on HOTS type questions, and the lack of practice on HOTS-oriented questions. In compiling HOTS questions, as many as 50% of students were able to make good questions in accordance with the HOTS questions preparation standards.